2007
DOI: 10.1080/13632460601155638
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Resistance Evaluation of Unreinforced Masonry Buildings

Abstract: The article presents seismic resistance evaluation study of unreinforced brick masonry buildings.The study was carried out as part of the Ph.D. research work of the first author. As part of the study, in addition to the standard laboratory tests, a dynamic field test was carried out on single-story, single-room unreinforced masonry structure. The model structure was tested in actual ground conditions against simulated earthquake vibrations produced through controlled explosions, especially designed for this pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Most modern buildings employ cement-based mortar, which consists primarily of one part cement and four to eight parts sand (Ali and Naeem 2007;Maqsood and Schwarz 2008a) and may contain locally available materials for improvement of mortar properties and reduction of cost. Mud or cement mortar is generally used to bond stones (Ali and Muhammad 2007), and in some cases no mortar is used at all, and wall cavities are filled with rubble to achieve an approximately level surface.…”
Section: Typologies Of Pakistan Unreinforced Masonry Buildingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most modern buildings employ cement-based mortar, which consists primarily of one part cement and four to eight parts sand (Ali and Naeem 2007;Maqsood and Schwarz 2008a) and may contain locally available materials for improvement of mortar properties and reduction of cost. Mud or cement mortar is generally used to bond stones (Ali and Muhammad 2007), and in some cases no mortar is used at all, and wall cavities are filled with rubble to achieve an approximately level surface.…”
Section: Typologies Of Pakistan Unreinforced Masonry Buildingsmentioning
confidence: 99%
“…Ali and Naeem (2007) conducted a dynamic field test on a single-story single-room URM structure to understand the seismic vulnerability of URM buildings in Peshawar (KP). Ahmad et al (2010) adopted a non-linear displacement-based approach to conduct earthquake loss estimation of URM buildings in Mansehra (KP) and predicted significant economic losses (collapse of 12-33% of houses) and human losses (injuries and deaths of 7-17% of the population).…”
Section: Introductionmentioning
confidence: 99%
“…The seismic response of masonry buildings either with reinforced concrete slab, ring/ bond beams, lintel beams, is mainly governed by the global mechanism primarily with shear response of the in-plane walls with limited energy dissipation capabilities and ductility (Javed et al 2006, Ali andNaeem 2007). The displacement-based method uses an equivalent nonlinear static SDOF system, called mechanical model in order to simulate analytically the response of an actual structure in terms of its displacement capacity, energy dissipation and secant vibration period.…”
Section: Nonlinear Static Single Degree Of Freedom (Sdof) System For mentioning
confidence: 99%
“…Post-earthquake surveys have shown that unreinforced masonry structure most of the time suffer out of plane local collapse mechanisms (Sorrentino 2008). In order to get reliable analysis, estimation of damping energy is crucial (Ali 2007). Therefore, in this study, damping ratio of fibrous plastered and unplastered wall were compared to evaluate the contribution of fibre within plastering of masonry walls.…”
Section: Introductionmentioning
confidence: 99%